Cultivating Leadership Attributes In Undergraduate Medical Education: A Mixed Method Study - Hareem Fatima; Muhammad Nasir Ayub Khan; Mahwish Niaz; Mahrukh Durrani; Shazia Irum; Muneeza Aamir Sami (Journal of Rawalpindi Medical College)
Objective: This research aimed to train undergraduate medical students through a feasible and achievable program and assess the effectiveness of integrating leadership training into the formal curricula of undergraduate medical education, aiming to enhance the development of leadership attributes and behaviours among medical students.